Amylin - Its role in the homeostatic and hedonic control of eating and recent developments of amylin analogs to treat obesity - Christina Neuner Boyle; Thomas Alexander Lutz; Christelle Le Foll (Elsevier, 2018)
Background: Amylin is a pancreatic β-cell hormone that produces effects in several different organ systems. One of its best-characterized effects is the reduction in eating and body weight seen in preclinical and clinical studies. Amylin activates specific receptors, a portion of which it shares with calcitonin gene-related peptide (CGRP). Amylin's role in the control of energy metabolism relates to its satiating effect, but recent data indicate that amylin may also affect hedonic aspects in the control of eating, including a reduction of the rewarding value of food. Recently, several amylin-based peptides have been characterized. Pramlintide (Symlin®) is currently the only one being used clinically to treat type 1 and type 2 diabetes. However other amylin analogs with improved pharmacokinetic properties are being considered as anti-obesity treatment strategies. Several other studies in obesity have shown that amylin agonists could also be useful for weight loss, especially in combination with other agents. Scope of review: This review will briefly summarize amylin physiology and pharmacology and then focus on amylin's role in food reward and the effects of amylin analogs in pre-clinical testing for anti-obesity drugs. Conclusion: We propose here that the effects of amylin may be homeostatic and hedonic in nature. Keywords: Amylin, CGRP, Homeostatic, Hedonic, Reward, Analog